2020
DOI: 10.1074/jbc.ra119.011122
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fluidity adjusts the insertion of the transacylase PlsX to regulate phospholipid biosynthesis in Gram-positive bacteria

Abstract: PlsX plays a central role in the coordination of fatty acid and phospholipid biosynthesis in Gram-positive bacteria. PlsX is a peripheral membrane acyltransferase that catalyzes the conversion of acyl-ACP to acyl-phosphate, which is in turn utilized by the polytopic membrane acyltransferase PlsY on the pathway of bacterial phospholipid biosynthesis. We have recently studied the interaction between PlsX and membrane phospholipids in vivo and in vitro Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 53 publications
0
22
0
8
Order By: Relevance
“…9). Since PlsX is a peripheral membrane protein that requires a negative charge on membrane surface for localization 21, 22 , we added 1-palmitoyl-2-oleyl-sn-glycero-3-phospho-rac-(1-glycerol) (POPG) in the lipid composition of GUV in the range of 0-50 % (% mol.) to observe that effect on the membrane localization.…”
Section: Resultsmentioning
confidence: 99%
“…9). Since PlsX is a peripheral membrane protein that requires a negative charge on membrane surface for localization 21, 22 , we added 1-palmitoyl-2-oleyl-sn-glycero-3-phospho-rac-(1-glycerol) (POPG) in the lipid composition of GUV in the range of 0-50 % (% mol.) to observe that effect on the membrane localization.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed mechanism of acyl-PO 4 channeling by PlsX remains to be defined, but our data allows us to speculate that it depends on the proper and stable insertion of PlsX in the membrane. This can be concluded from the biophysical analysis of the PlsX L254E mutant presented in the accompanying paper (33), which showed that this protein can interact with membranes only superficially. A similar conclusion is also supported by in vivo experiments, which showed that the phenotype of the PlsX L254E mutant is not much worse than the phenotype of a strain in which PlsX can never access the membrane (PlsX L254E -HBsu) (Fig.…”
Section: Catalytic and Channeling Roles Of Plsxmentioning
confidence: 86%
“…4A, compare spots of PlsX L254E and the parental depletion strain). Furthermore, a detailed biophysical analysis of the PlsX L254E mutant showed that it still retains the ability to bind superficially to membranes, probably via electrostatic interactions (33). Therefore, it is certainly possible that the cytoplasmic molecules of PlsX L254E will exhibit transient or superficial contact with the membrane sufficient to allow some transfer of acyl-PO 4 to the bilayer and maintain a low level of phospholipid synthesis.…”
Section: Mistargeting As a Way To Test The Role Of Membrane Localization In Plsx Functionmentioning
confidence: 99%
“…The membrane as a bacterial thermometer was demonstrated by several studies in the de Mendoza lab. The rigid or fluid state of membrane lipids is transmitted to membrane proteins by affecting their conformation and/or localization [10,11]. In S. aureus, membrane fluidity affects expression of virulence factors [12].…”
Section: New Lines Of Exploration Arising From the Dead-membrane Connectionmentioning
confidence: 99%